2022
DOI: 10.3390/biom12071011
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Dimensions, More Structures for Improved Discrete Models of Dynamics of Free versus Antigen-Bound Antibody

Abstract: Over the past decade, Markov State Models (MSM) have emerged as powerful methodologies to build discrete models of dynamics over structures obtained from Molecular Dynamics trajectories. The identification of macrostates for the MSM is a central decision that impacts the quality of the MSM but depends on both the selected representation of a structure and the clustering algorithm utilized over the featurized structures. Motivated by a large molecular system in its free and bound state, this paper investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…The experimental techniques showing distal effects include circular dichroism, 33 nuclear magnetic resonance, 34 fluorescence correlation microscopy, 20 hydrogen-deuterium exchange mass spectrometry (HDX), 20 , 35 electron microscopy, 35 and crystallography, 36 and are further supported by extensive molecular dynamics simulations. 37 , 38 Relevant to observations in this study, crystallography studies have also demonstrated that distal loops in the CH1 domain exist in different conformations when antibodies are free versus bound to antigen, 39 and can be transmitted through linkers thought to be passive. 40 Similarly, changes in both crystal structures and the relative population of distinct conformational states of IgG related to factors such as post-translational modification have been widely reported.…”
Section: Discussionsupporting
confidence: 71%
“…The experimental techniques showing distal effects include circular dichroism, 33 nuclear magnetic resonance, 34 fluorescence correlation microscopy, 20 hydrogen-deuterium exchange mass spectrometry (HDX), 20 , 35 electron microscopy, 35 and crystallography, 36 and are further supported by extensive molecular dynamics simulations. 37 , 38 Relevant to observations in this study, crystallography studies have also demonstrated that distal loops in the CH1 domain exist in different conformations when antibodies are free versus bound to antigen, 39 and can be transmitted through linkers thought to be passive. 40 Similarly, changes in both crystal structures and the relative population of distinct conformational states of IgG related to factors such as post-translational modification have been widely reported.…”
Section: Discussionsupporting
confidence: 71%
“…An essential one in this direction is to move from a single-structure to a multi-structure view of protein molecules as obtaining a detailed understanding of the structure and dynamics of unbound and bound molecular systems remains a fundamental challenge. In [ 4 ], Kabir et al investigated the utility of a coarse-grained representation (based on ultrafast shape recognition) as a better state space discretization to obtain Markov State models of a higher quality with the capability to capture the multi-view structural dynamics of biological molecules and their complex, even in the absence of the associated energetics.…”
mentioning
confidence: 99%